THE INTERNET AS A TOOL FOR TRAINING AND INFORMATION FOR ENVIRONMENTAL EDUCATORS IN THE CONTEXT OF THE PANDEMIC - Morais, Enoque Gomes de (Geosaberes; Vol 15 (2024)DO - 10.26895/geosaberes.v15i0.1277, 2024)
The virtual space makes available to its users a diverse range of content and information, including channels aimed at Environmental Education. Therefore, this work was sought through surveys on the world wide web, through various communication channels, investigate channels that provide content for training and information for environmental educators. These contents are available exclusively for free, configured as training courses in Environmental Education or related to the environment, with the aim of helping, in these different investigations, those seeking new knowledge or improving existing ones.